2018
DOI: 10.1371/journal.pone.0203068
|View full text |Cite|
|
Sign up to set email alerts
|

Allelic variation of vernalization and photoperiod response genes in a diverse set of North American high latitude winter wheat genotypes

Abstract: The major physiological determinants of wheat (Triticum aestivum L.) phenology in a given area are a response to vernalization temperature and day length, which are at least in part, regulated by the allelic variation at the vernalization (VRN) and photoperiod (PPD) loci, respectively. Characterization of the existing genetic variation for plant phenology in winter wheat can assist breeding programs improve adaptation to local environments and to optimize wheat phenology for the changing climate. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 52 publications
2
31
0
1
Order By: Relevance
“…Dominant alleles at these loci lead to a spring type growth habit (the transition to the generative phase in such plants occurs without exposure to low positive temperatures) and contain mutations in the promoter and/or the 1st intron relative to alleles of the wild type [ 33 – 36 ]. In regions with cold climates, including Western and Eastern Siberia, for spring wheat with dominant alleles associated with a spring habit ( Vrn-A1a in combination with Vrn-B1a or Vrn-B1c ), this combination allows the plant to complete its lifecycle after a relatively short vegetative period and escape autumn frosts [ 37 39 ]. For southern latitudes, varieties with one allele of Vrn-B1a or Vrn-D1a can have a definite advantage, as they ripen later, and a longer vegetative period can provide higher yields [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dominant alleles at these loci lead to a spring type growth habit (the transition to the generative phase in such plants occurs without exposure to low positive temperatures) and contain mutations in the promoter and/or the 1st intron relative to alleles of the wild type [ 33 – 36 ]. In regions with cold climates, including Western and Eastern Siberia, for spring wheat with dominant alleles associated with a spring habit ( Vrn-A1a in combination with Vrn-B1a or Vrn-B1c ), this combination allows the plant to complete its lifecycle after a relatively short vegetative period and escape autumn frosts [ 37 39 ]. For southern latitudes, varieties with one allele of Vrn-B1a or Vrn-D1a can have a definite advantage, as they ripen later, and a longer vegetative period can provide higher yields [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are currently developing germplasm to test the effect of the additional missense mutations on senescence in field trials. It is known that allelic variation within populations can account for variable success across environments [3941]. Indeed, previous studies of natural variants in NAM-A1 identified a missense mutation (haplotype NAM-A1c) which was associated with an intermediate grain protein content phenotype between the wild-type allele and a third haplotype containing the missense mutation in tandem with a frame-shift mutation in the C-terminal domain [42].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they can be used to identify broad differences in cultivar LT tolerance genetic potential. These indicators can be as simple as LT 50 determinations on field acclimated plants sown on the optimum date in the autumn (Fowler, Gusta, & Tyler, 1981) to molecular markers for major developmental and LT tolerance genes (see references in Fowler, N'Diaye, Laudencia‐Chingcuanco, & Pozniak, 2016; Kippes et al., 2018; Whittal, Kaviani, Graf, Humphreys, & Navabi, 2018). However, LT acclimation and vernalization analyses for these indicators have revealed significant unexplained variability suggesting there are large number of additional small effect genes involved in the regulation of critical metabolic pathways and cellular processes (Laudencia‐Chingcuanco et al., 2011).…”
Section: Applicationmentioning
confidence: 99%